P44 Chronic obstructive pulmonary disease exacerbation and respiratory acidosis: patient outcomes at 6 months. (12th November 2015) - Jackson, S; McKeever, TM; Hearson, G; Housley, G; Reynolds, C; Kinnear, W; Harrison, TW; Kelly, AM; Shaw, DE
Abstract : Introduction: Recognition of hypercapnic respiratory failure is a vital part of the assessment and management of the patient with an acute exacerbation of chronic obstructive pulmonary disease (COPD). Several studies have demonstrated that respiratory acidosis in the context of an acute exacerbation is associated with worse inpatient outcomes. Our study compares the outcomes of patients admitted with an acute exacerbation, between those with respiratory acidosis and those who had a normal pH and PaCO2 on arterial blood gas (ABG) analysis. Methods: Patients requiring hospital treatment for an acute exacerbation of COPD had an ABG taken on admission. Patients were subsequently assessed for the following outcomes: inpatient mortality, outpatient mortality up to six months after discharge and hospital re-admission rates in the six months post discharge. Chi-squared test was applied to assess the relationship between respiratory acidosis and our outcomes. Results: 234 patients had an admission ABG and were subsequently followed up to the point of death or six months post discharge. Patients with a PaCO2 of >6 Kpa were 2.33 times (95% CI 1.11 to 4.96) more likely to die in hospital as compared to those patients with a normal value. Patients with a lower arterial pH (<7.35) were 2.32 times (95% CI 1.07 to 4.96) more likely to die in hospital as compared to those with a pH of >7.35. The increased risk in mortality was only seen for in-hospital mortality and there was no association with death in the 6 months following discharge, hospital re-admission or re-admission for a respiratory problem. Conclusion: This data supports previous studies that suggest hypercapnia and respiratory acidosis are associated with increased inpatient mortality, therefore further demonstrating the usefulness of pH and PaCO2 as prognostic markers for inpatient outcomes. However our study does suggest that patients with respiratory acidosis on admission, who survive until discharge from hospital, do not have an increased risk of six month mortality or readmission compared to those with a normal admission ABG.